A possible heating mechanism for the X-ray-emitting plasma within clusters of galaxies. (18th March 2013) - BINGHAM, R.; KELLETT, B. J.; DE ANGELIS, U.; TSYTOVICH, V. N.; SHUKLA, P. K.
Abstract: X-ray and extreme ultraviolet emission from galaxy clusters can be interpreted as thermal emission from a hot plasma gravitationally bound to the cluster and constituting a significant amount of the mass of the cluster. The origin of this plasma and its thermal energy content can be linked to the formation process through the theory of self-organization of these structures.